Clostridium difficile infection in the absence of a colon. (21st October 2010) - Khan, Mohid S; Levy, D; Mann, S
Abstract : Clostridium difficile (CD) infection is almost always confined to the colon causing a spectrum of illness ranging from diarrhoea to fulminant colitis. CD infection of the small intestine has been described but the identification of CD toxin in the stoma effluent of a patient with an end ileostomy is rare. We describe a 91-year-old woman, with a history of proctocolectomy for ulcerative colitis, presenting with profuse ileostomy diarrhoea after a course of antibiotics. Ileostomy effluent was positive for CD toxin but the patient died despite appropriate treatment. This suggests that the small intestine is susceptible to CD infection in antibiotic-treated patients many years after a colectomy. CD enteritis should be considered in all patients with increased ileostomy diarrhoea despite the absence of a colon.